THE INFLUENCE OF THE HUMAN DEVELOPMENT INDEX, OPEN UNEMPLOYMENT RATE, AND INFLATION ON ECONOMIC GROWTH IN INDONESIA - Dhini Mahtura; Ichsan (LPPM Universitas Malikussaleh, 2026)
Indonesia's economic growth over the past three decades has shown a downward trend, indicating a reduction in the national economic growth rate due to various structural changes and economic challenges faced. This study aims to determine the effect of the human development index (HDI), the open unemployment rate (OUR), and inflation on economic growth in Indonesia. This study uses time series data from 1994-2024, using Multiple Linear Regression analysis. The results of the data analysis show that HDI has a negative and significant effect on economic growth in Indonesia, OUR has a negative and insignificant effect on economic growth, and inflation has a negative and significant effect on economic growth. Simultaneously, HDI, OUR, and inflation have a significant effect on economic growth in Indonesia. The government is expected to balance improving the quality of human resources, price stability. And job creation to support economic growth in indonesia.